2021
DOI: 10.20944/preprints202106.0470.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

River Influx Drives Heavy Metal Pollution in Manila Bay, Philippines: An Insight from Multivariate Analyses

Abstract: Recent work on heavy metal pollution in Manila Bay suggests elevated concentration in the surface sediments. It is critical to identify the sources of these heavy metals to effectively rehabilitate the bay. Our study investigated the sources of the heavy metal pollution that ended up in Manila Bay and the risks associated with these toxic metals based on a recent survey conducted. Surface sediment samples with higher heavy metal concentrations were found in the upper to middle parts of the bay while lower conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Theta (P.3) variant, additionally referred to as GR/1092K.V1 contains key spike mutations (141-143 deletion E484K; N501Y; and P681H) and changed into first detected withinside the Philippines and Japan in February 2021 [88]. Study done by Diwa, R et al [89] showed that heavy metal pollution in Manila Bay is due to several rivers flowing northeast of Manila Bay, especially the Marilao Meycauayan Obando River System. It is ranked as one of the 30 dirtiest river systems in the world.…”
Section: Cases Of Eta Variantmentioning
confidence: 99%
“…Theta (P.3) variant, additionally referred to as GR/1092K.V1 contains key spike mutations (141-143 deletion E484K; N501Y; and P681H) and changed into first detected withinside the Philippines and Japan in February 2021 [88]. Study done by Diwa, R et al [89] showed that heavy metal pollution in Manila Bay is due to several rivers flowing northeast of Manila Bay, especially the Marilao Meycauayan Obando River System. It is ranked as one of the 30 dirtiest river systems in the world.…”
Section: Cases Of Eta Variantmentioning
confidence: 99%
“…To identify the sources of these heavy metals, we performed multivariate analyses such as HCA, PCA, and Pearson correlation analysis. These are useful tools for finding the causes of heavy metal pollution by grouping them according to similarity in their sources [12][13][14]25,[37][38][39]. HCA grouped the sampling areas into 3 clusters.…”
Section: Heavy Metal Concentration and Source Identificationmentioning
confidence: 99%
“…While existing research were conducted to assess the extent of mercury contamination in the surrounding area of the abandoned mine, detailed health and environmental impacts of ad mixture of the heavy metals and their possible origins remain unknown. Therefore, this study employed multivariate analyses, such as hierarchical cluster analysis (HCA) and principal component analysis (PCA), to determine the possible ecological and health risks associated to the heavy metals in soils and sediments [11][12][13][14]. To our knowledge, this is the most detailed study on the long-term health impact and source apportionment of heavy metals in the island paradise billed as "one of the most beautiful islands in the world" [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation